PROFITABILITY AND TURNOVER APPRAISAL OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - Terry Keme Zuode Odogu; Amapamo Stephen Koroye (Gusau Journal of Accounting and Finance)
The study seeks to appraise the performance of deposit money banks in Nigeria, given the mounting pressure for cashless transactions and the increasing digitization and automation of financial services around the globe. Appropriately, the ex-post facto/casual comparative research design was adopted to obtain relevant and desirable secondary data from the Annual Bulletins of the Central Bank of Nigeria and E-payment Statistics Platforms from 2012 to 2020, to empirically appraise the profitability and turnover of all the 15 Nigerian deposit money banks quoted as at January 1, 2021, in the light of the non-bank led theory. Specifically, the study interrogates the effect of point of sale and online loans on the profitability and turnover of Nigerian deposit money banks, using Pearson Product Moment Correlation and Linear Regression Analysis. The conclusions from findings from E-View 9.0 (inferential) statistical results at 0.05 level of significance are that, while the increasing use and patronage of point-of-sale terminals significantly improves the profitability of Nigerian deposit money banks, it adversely affects their turnover insignificantly; and the flexibility of and increasing preference for online loan facilities adversely affect the profitability, but improves the turnover of deposit money banks in Nigeria. The study recommends that deposit money banks should be operationally flexible and competitive, and fully automate their financial products and services.